The competitive landscape of online platforms - Néstor Duch-Brown (European Commission, Joint Research Centre (JRC), 2017)
This paper describes the different forces that shape the market structure of four different 'online platform ecosystems' and the competition between them. The paper focuses on the following categories of platforms, which represent a wide scope of online activities: (i) e-commerce marketplaces; (ii) app stores; (iii) social media; and (iv) online advertising platforms. A central concern is to provide descriptive, empirical evidence on the relative strength of the forces operating in each case. In the past decade or so, many theoretical and conceptual contributions have been very helpful in developing a clear understanding of many of the issues around multi-sided markets, and have analysed these activities from many different perspectives. Unfortunately, they have provided hardly any empirical evidence. This paper attempts to reduce the lack of empirical evidence available on online platforms.
Keywords: D23; K11; K12; L86; 330; digital single market; data economy; online platforms; multi-sided markets